2004
DOI: 10.1080/00102200490487535
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF OXYGEN ON NOxREMOVAL IN CORONA DISCHARGE FIELD: NOxBEHAVIOR WITHOUT A REDUCING AGENT

Abstract: A DeNO x process using a DC corona discharge was investigated experimentally. A mixture system of N 2 =O 2 =NO was used as a test gas. The compositions such as NO, NO 2 , N 2 O and so on were analyzed with Fourier transform infrared spectroscopy and an NO x meter. It was found that the characteristics of NO removal by corona discharge differed remarkably whether or not oxygen exists in the mixture. In regard to the spectrum of light emission from the corona discharge in N 2 atmosphere or N 2 =O 2 mixture, some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Therefore, plasma has not been powerful enough to make any significant variation in nitrogen oxide concentrations before this point. It was found that NO is oxidised to NO 2 due to the existence of different active oxygen species and ozone as it is reported on previous studies (Mohapatro and Rajanikanth 2011;Arai et al 2004;Fitzsimmons et al 1999). NO concentration decreased by 72 % and NO 2 concentration increased by 77 % by applying maximum voltage at 13.5 kV during the experiments.…”
Section: Effect Of Non-thermal Plasma On No X Concentrationsupporting
confidence: 54%
See 1 more Smart Citation
“…Therefore, plasma has not been powerful enough to make any significant variation in nitrogen oxide concentrations before this point. It was found that NO is oxidised to NO 2 due to the existence of different active oxygen species and ozone as it is reported on previous studies (Mohapatro and Rajanikanth 2011;Arai et al 2004;Fitzsimmons et al 1999). NO concentration decreased by 72 % and NO 2 concentration increased by 77 % by applying maximum voltage at 13.5 kV during the experiments.…”
Section: Effect Of Non-thermal Plasma On No X Concentrationsupporting
confidence: 54%
“…Furthermore, emission reduction in diesel engines at low temperature is important in some special applications of diesel engines such as mining industries where exhaust cooling occurs for safety reasons. In comparison with the numerous publications on NO x treatment by plasma (Lebouvier et al 2011;Vinh et al 2012;Arai et al 2004;Jolibois et al 2012;Mohapatro and Rajanikanth 2011;Chae 2003;Yoshida et al 2009), a limited amount of research has investigated particulate matter (Ye et al 2005;Thomas et al 2000;Babaie et al 2013) and most of it has emphasised PM mass reduction only (Yao et al 2006;Fushimi et al 2008). In this paper, the effect of plasma technique on particulate matter constitutes (soot, SOF and sulphates) and NO, NO 2 and N 2 O emission concentrations have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ozone will be consumed through different reactions in plasma state. For example, the ozone will be consumed by the following reactions for NO x reduction in plasma exhaust treatment [13,32]: Note that the atomic nitrogen (N) can be produced due to the dissociation of nitrogen and/or NO molecules by high energy electrons in plasma state [3] and NO 3 , which is an unstable compound, usually turns into NO and NO 2 in the environment [33].…”
Section: Effect Of Ntp On Ozone Concentrationmentioning
confidence: 99%
“…Ozone can participate in many reactions in plasma treated gas. The main reaction for ozone production in the plasma state is the reaction of the O radical with oxygen, based on the following reaction [32]:…”
Section: Effect Of Ntp On Ozone Concentrationmentioning
confidence: 99%
“…NO conversion processes in plasma have been experimentally investigated by many researchers in terms of various operating parameters including reactor geometry (Mizuno et al, 1995;Wu et al, 2005), power supply (Matsumoto et al, 2010;Mok et al, 1998), polarity (Masuda and Nakao, 1990), gas composition (Arai et al, 2004;Sun and Yin, 2009), temperature (Eichwald et al, 2002) and additives (Cha et al, 2007;Lin et al, 2010). Kinetic models were also introduced to understand the mechanism of plasmainduced NOx conversion (Mok and Ham, 1997;Orlandini and Riedel, 2000).…”
Section: Introductionmentioning
confidence: 99%